Is Yemen a new model? an interview with Jamal Benomar. (New York, NY Columbia University, 2013)
“In July 2010, New York Times foreign correspondent Robert F. Worth published an article titled “Is Yemen the Next Afghanistan?” Worth argued that the region was “lawless” and “chronologically a war zone,” especially after the resurgence of AI Qaeda’s operations in the country. Yemeni president Ali Abdullah Saleh, Worth said, was running the country “like a sheik: using his own tribe as a power base and constantly making deals to head off his rivals.” Almost a year later, during the Arab Spring revolutions, Saleh was overthrown after thirty-three years in power. Since then, Yemen has been undergoing a democratic transition, and today, under President Abdo Rabu Masour Hadi, it is debating the shape of its future government through the UN-backed National Dialogue Conference. For the first time, women have a seat at the negotiation table. The Journal spoke with Jamal Benomar, the UN Special Adviser on Yemen, about the National Dialogue Conference and how it has succeeded in bringing new actors to the political process”
Keywords: Benomar, Jamal -- [1957-].; Citizenship -- Yemen; Dictatorship -- Yemen; Equality -- Yemen; Human rights -- Yemen; International law (Islamic law) -- Yemen; Islamic leadership -- Yemen; Man-woman relationships -- Yemen; Peace movements -- Yemen; Religion and the humanities -- Yemen; Yemen -- Politics and government